2000
DOI: 10.1073/pnas.040559697
|View full text |Cite
|
Sign up to set email alerts
|

The xeroderma pigmentosum group C gene leads to selective repair of cyclobutane pyrimidine dimers rather than 6-4 photoproducts

Abstract: , whereas the fully corrected XP4PA-SE2 cells regained normal CPD and 6-4PP repair capacities. We also exposed pRSVcat plasmid to UVC (to induce CPD and 6-4PP), to UVC ؉ photolyase (to leave only 6-4PP on the plasmid), or to UVB ؉ acetophenone (to induce only CPD). Host cell reactivation of UVB ؉ acetophenone-, but not of UVC ؉ photolyase-treated plasmids was normal in XP4PA-SE1 cells. Thus, increasing XPC gene expression leads to selective repair of CPD in the global genome. Undetectable XPC protein is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
2
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 47 publications
7
52
2
2
Order By: Relevance
“…The XPC protein recognizes a variety of bulky DNA damages including UV-caused cyclobutane pyrimidine dimers and cisplatin-generated interstrand crosslinks (ICL) [9][10][11][12][13][14][15][16]. The XPC protein binds tightly with an HR23B protein to form a stable XPC-HR23B complex [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The XPC protein recognizes a variety of bulky DNA damages including UV-caused cyclobutane pyrimidine dimers and cisplatin-generated interstrand crosslinks (ICL) [9][10][11][12][13][14][15][16]. The XPC protein binds tightly with an HR23B protein to form a stable XPC-HR23B complex [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…They may have different affinities for each type of UV damage and might need DDB2 for recruitment to CPD, whereas XPC efficiently recognizes 6-4PPs (4,37). Nevertheless, Emmert et al (38) reported that a truncated XPC protein leads to repair of CPDs but not of 6-4PPs. Our data indicate that the ability to repair both types of DNA damage may depend on the amount of available XPC protein.…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction and Western-blot analysis with chemiluminescent detection were as described by Emmert et al (2000). The following antibodies and dilution factors were used: mouse anti-XPC (1:3000), mouse-actin (H-196, Santa Cruz, Santa Cruz, CA, USA, 1:50 000) and antimouse peroxidase-conjugated immunoglobulin G (IgG-HRP, Santa Cruz, 1:5000).…”
Section: Rnai and Bap Treatmentmentioning
confidence: 99%